Shifting temporal trends and disparities in sarcoidosis mortality in the United States: A retrospective analysis from 1999 to 2020. - Fatima Ali Raza; Sumeet Kumar; Ayesha Mohammad; Areej Amin; Farooq Ahmad; Sohaib Tousif; Urwah Kamran; Lamea Bint Sahab; Sajjad Ali; Mah I Kan Changez; Aman Goyal (PLoS ONE)
Introduction Sarcoidosis is an inflammatory disease characterized by granulomas, the etiology of which remains unclear. This study examines sarcoidosis-related mortality trends in the United States from 1999 to 2020, with a focus on disparities pertaining to patient sex, geographical location, and urbanization status. Methods We analyzed death certificate data from the CDC WONDER database, using ICD-10 code D86. Age-adjusted mortality rates (AAMR) per 1,000,000 people were calculated. Trends were analyzed using Joinpoint regression models to determine annual percentage changes (APC). Results A total of 37,956 Sarcoidosis-related deaths were documented from 1999 to 2020 in the United States. The AAMR increased from 3.9 in 1999 to 6.4 in 2020. Significant mortality increases were observed from 1999-2001 and again from 2018-2020. Mortality rates were consistently higher among women compared to men. A significant difference in AAMR was observed across states, with highest mortality in the South region and lowest in the West region. Urbanization trends shifted from higher AAMR rates in metropolitan to non-metropolitan areas post-2018. Non-Hispanic Black individuals experienced the highest mortality rates throughout the study period. Conclusions This study highlights significant racial and geographic disparities in sarcoidosis-related mortality. Women, Black patients, and those residing in non-metropolitan areas are at the highest risk for Sarcoidosis associated mortality. Targeted public health interventions are required to address these prevalent disparities.